2019
DOI: 10.1183/13993003.01908-2018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial design and new therapies for pulmonary arterial hypertension

Abstract: Until 20 years ago the treatment of pulmonary arterial hypertension (PAH) was based on case reports and small series, and was largely ineffectual. As a deeper understanding of the pathogenesis and pathophysiology of PAH evolved over the subsequent two decades, coupled with epidemiological studies defining the clinical and demographic characteristics of the condition, a renewed interest in treatment development emerged through collaborations between international experts, industry and regulatory agencies. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
149
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(160 citation statements)
references
References 101 publications
(108 reference statements)
1
149
0
10
Order By: Relevance
“…To date, trials in patients based on genetically isolated targets have been focused on use of the calcineurin inhibitor tacrolimus which, among other effects, activates BMP signalling to reverse vascular occlusion in rat models, and seems to be well tolerated in patients with PAH 111 . Although preliminary in vitro findings support the potential restoration of potassium channel activity after pharmacological intervention in loss-of-function KCNK3 and ABCC8 cell models, further preclinical testing is required to evaluate the feasibility of manipulating these targets for patient benefit 36,97,112 .…”
Section: [H1] Clinical Implicationsmentioning
confidence: 99%
“…To date, trials in patients based on genetically isolated targets have been focused on use of the calcineurin inhibitor tacrolimus which, among other effects, activates BMP signalling to reverse vascular occlusion in rat models, and seems to be well tolerated in patients with PAH 111 . Although preliminary in vitro findings support the potential restoration of potassium channel activity after pharmacological intervention in loss-of-function KCNK3 and ABCC8 cell models, further preclinical testing is required to evaluate the feasibility of manipulating these targets for patient benefit 36,97,112 .…”
Section: [H1] Clinical Implicationsmentioning
confidence: 99%
“…A related shortcoming of appraised studies is the choice of outcomes analyzed, which was found to be selective, incomprehensive, and usually not accompanied by clear justification. The most commonly assessed outcome was 6MWDdespite failure of multiple studies to consistently establish significant associations between 6MWD and clinically more relevant outcomes such PAH-related hospitalization, lung transplantation, initiation of rescue therapy or death [28,29,44,52,86,87]. Moreover, the assessed evidence synthesis studies generally neither presented a review of the outcome definitions and outcome measures of included trials, nor an assessment of imputation rules for handling missing data.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, morbidity and mortality event trials require a large number of subjects in order to demonstrate effects even as early as 1 year [59,60]. Looking to the future, consideration should be given to including 6MWD, FC, and BNP/NT-proBNP in the assessment of time to clinical improvement, a new endpoint proposed at the recent 6th World Symposium on Pulmonary Hypertension [61].…”
Section: Discussionmentioning
confidence: 99%